Molybdenum-based microwave dielectric ceramic material and preparation method and application thereof

By adopting the structure and preparation process of the molybdenum-based microwave dielectric ceramic material NaX (MoO4)2, the problem that existing ceramic materials cannot meet the performance requirements of the new generation of wireless systems is solved, and ceramic materials with excellent microwave dielectric properties are prepared at a lower sintering temperature and remain stable in the air.

CN119661221APending Publication Date: 2025-03-21XIDIAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411882620.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing electronic ceramic materials cannot meet the requirements of new generation wireless systems (5G and 6G) ​​for lower sintering temperature, low dielectric loss, low dielectric constant and near zero resonance frequency temperature coefficient, and have poor stability, making it difficult to achieve large-scale industrial production.

Method used

The structural expression of the general formula NaX (MoO4)2 is adopted using the molybdenum-based microwave dielectric ceramic material, where X is one or more of Pr, Sm, and Eu, and is prepared by ball milling and tablet sintering process. The sintering temperature is between 800 and 900°C, and high-quality sintering can be achieved at a lower temperature.

Benefits of technology

The preparation of ceramic materials at a lower sintering temperature is achieved, with excellent microwave dielectric properties, including low dielectric constant, high quality factor and near zero resonant frequency temperature coefficient, and is stable in air, and is suitable for the preparation of low-temperature co-fired ceramic substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661221A_ABST
    Figure CN119661221A_ABST
Patent Text Reader

Abstract

The invention relates to a molybdenum-based microwave dielectric ceramic material and a preparation method and application thereof. The structural expression general formula of the ceramic material is NaX (MoO4) 2, and X is one or more of Pr, Sm and Eu. The preparation method of the ceramic material comprises the following steps: S1, weighing Na2CO3, MoO3 and rare earth oxide as raw materials according to a structural expression general formula NaX (MoO4) 2 of the ceramic material; s2, uniformly mixing the raw materials through a primary ball-milling process to obtain primary ball-milled powder; s3, the primary ball-milled powder is pre-sintered, and pre-sintered ceramic powder is obtained; s4, performing secondary ball milling on the ceramic powder to obtain secondary ball-milled powder; and S5, tabletting and sintering the secondary ball-milled powder through a tabletting and sintering process to obtain the ceramic material. The ceramic material can be prepared by sintering in a relatively low sintering temperature range, has a relatively low dielectric constant, a relatively high quality factor and a near-zero temperature coefficient of resonance frequency, and shows excellent microwave dielectric properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic ceramic material preparation, and specifically relates to a molybdenum-based microwave dielectric ceramic material and a preparation method and application thereof. Background Art

[0002] The new generation of wireless systems (5G and 6G) ​​provide faster and more reliable broadband access with greater capacity and lower latency. These characteristics require microwave dielectric materials to have lower sintering temperature (<960°C), lower dielectric loss (i.e., high quality factor Qf, tanδ=1 / Q<0.001), lower dielectric constant (ε r <15), and a near-zero resonant frequency temperature coefficient to ensure high-quality manufacturing of components.

[0003] However, most traditional electronic ceramics cannot meet the above performance requirements. The reason is that the sintering temperature of most electronic ceramics is too high to be co-fired with metal electrodes with lower melting points. At the same time, most ceramic materials currently have poor stability and serious performance deterioration when placed in the air, making it difficult to achieve large-scale industrial production. The development of electronic ceramic materials with low temperature, good stability and good microwave performance, especially low loss and low dielectric constant, has aroused people's interest.

[0004] There are four main ways to achieve low-temperature sintering of microwave dielectric ceramics: 1. Doping with an appropriate amount of sintering aids - low-melting oxides or low-melting glass; 2. Using wet chemical methods to prepare powders with high surface activity; 3. Using nanopowders; 4. Using hot pressing sintering. Among the above methods of reducing the sintering temperature, considering the production cost and the complexity of the process, methods 2, 3, and 4 are not conducive to industrial production. Method 1 is low-cost and simple in process, and is currently a commonly used low-temperature sintering method, but additives often deteriorate the performance of ceramics.

[0005] Therefore, finding new microwave dielectric ceramic systems with low inherent sintering temperatures is one of the future development directions. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention provides a molybdenum-based microwave dielectric ceramic material and a preparation method and application thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:

[0007] An embodiment of the present invention provides a molybdenum-based microwave dielectric ceramic material, wherein the general structural expression formula of the ceramic material is NaX(MoO4)2, wherein X is one or more of Pr, Sm, and Eu.

[0008] In one embodiment of the present invention, the sintering temperature of the ceramic material is 800-900°C.

[0009] In one embodiment of the present invention, the dielectric constant of the ceramic material is 8 to 13, the quality factor is 50,000 to 100,000 GHz, and the resonant frequency temperature coefficient is -30 to -50 ppm / °C.

[0010] Another embodiment of the present invention provides a method for preparing a molybdenum-based microwave dielectric ceramic material, comprising the steps of:

[0011] S1. According to the general formula NaX(MoO4)2 of the ceramic material structure, weigh Na2CO3, MoO3 and rare earth oxide as raw materials, wherein X is one or more of Pr, Sm and Eu, and the rare earth oxide includes one or more of Pr2O3, Sm2O3 and Eu2O3;

[0012] S2, mixing the raw materials uniformly through a primary ball milling process to obtain a primary ball milled powder;

[0013] S3, pre-sintering the primary ball-milled powder to obtain a pre-sintered ceramic powder;

[0014] S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder;

[0015] S5. The secondary ball-milled powder is pressed and sintered by a pressing and sintering process to obtain the ceramic material.

[0016] In one embodiment of the present invention, step S1 includes:

[0017] The rare earth oxide is placed in a muffle furnace and kept at 700-850° C. for 3-6 hours.

[0018] In one embodiment of the present invention, step S2 comprises:

[0019] The raw materials, zirconium balls and anhydrous ethanol are added into a ball mill in a mass ratio of 1:2:1 and ball milled once to mix them evenly. The parameters of the first ball milling include: a rotation speed of 200 to 400 r / min and a time of 3 to 6 hours to obtain the first ball milled powder.

[0020] In one embodiment of the present invention, step S3 includes:

[0021] The once ball-milled powder is dried, and the dried powder is pre-sintered at 600-650° C. for 4-8 hours to obtain a pre-sintered ceramic powder.

[0022] In one embodiment of the present invention, step S4 includes:

[0023] The ceramic powder is first ground into powder, and then put into a ball mill for secondary ball milling. The secondary ball milling parameters include: a rotation speed of 200 to 400 r / min and a time of 3 to 6 hours to obtain the secondary ball milled powder.

[0024] In one embodiment of the present invention, step S5 includes:

[0025] The secondary ball-milled powder is dried, and 5-8% by weight of PVA is added to the dried powder for granulation. After granulation, the powder is sieved to 60-120 mesh, and pressed into a ceramic green body at a pressure of 200-300 MPa in an electric press, and the ceramic green body is kept at 500-600° C. for 4-6 hours to remove PVA, and finally kept at 800-900° C. for 6-8 hours for sintering to obtain the ceramic material.

[0026] In one embodiment of the present invention, there is provided an application of a molybdenum-based microwave dielectric ceramic material in a low-temperature co-fired ceramic substrate.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The molybdenum-based microwave dielectric ceramic material NaX(MoO4)2 of the present invention can be sintered within a relatively low sintering temperature range, has a relatively low dielectric constant, a relatively high quality factor and a near-zero resonant frequency temperature coefficient, and exhibits excellent microwave dielectric properties; the ceramic material has good stability when placed in the air, and has the characteristics of simple chemical composition, simple preparation process, environmental protection, non-toxicity and pollution-free; the ceramic material can be co-fired with Ag electrodes or Al electrodes, and is suitable for the preparation of low-temperature co-fired ceramic substrates, and has broad application potential in the fields of microwave resonators, filters and flat antennas. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic flow chart of a method for preparing a molybdenum-based microwave dielectric ceramic material provided in an embodiment of the present invention;

[0030] Figure 2 The Na sintered at 740-920°C provided in the embodiment of the present invention 0.5 Pr 0.5 Schematic diagram of the density and relative density of MoO4 ceramics changing with temperature;

[0031] Figure 3 The Na sintered at 740-920°C provided in the embodiment of the present invention 0.5 Pr 0.5 Schematic diagram of the microwave dielectric properties of MoO4 ceramics changing with sintering temperature;

[0032] Figure 4A schematic diagram showing the change of density and relative density of NaSm(MoO4)2 ceramic sintered at 740-950°C with temperature provided in an embodiment of the present invention;

[0033] Figure 5 A schematic diagram showing the variation of microwave dielectric properties of NaSm(MoO4)2 ceramics sintered at 740-950°C with temperature provided in an embodiment of the present invention;

[0034] Figure 6 The XRD patterns of the samples in Example 1, Example 2 and Example 3 provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0036] This embodiment provides a low-loss, low-dielectric molybdenum-based microwave dielectric ceramic material, the general structural expression formula of the ceramic material is NaX(MoO4)2, wherein X is one or more of Pr, Sm, and Eu.

[0037] Specifically, the low-loss and low-medium molybdenum-based microwave dielectric ceramic material can be NaPr(MoO4)2, NaSm(MoO4)2, NaEu(MoO4)2, NaPr 0.5 Sm 0.5 (MoO4)2、NaPr 0.5 Eu 0.5 (MoO4)2、NaSm 0.5 Eu 0.5 (MoO4)2、NaPr 1 / 3Sm 1 / 3 Eu 1 / 3 Any one of (MoO4)2.

[0038] Specifically, the sintering temperature of the ceramic material is 800-900° C., and the ceramic material can be sintered within a relatively low sintering temperature range. It should be noted that 800-900° C. is the sintering temperature at which the NaX(MoO4)2 system achieves better performance.

[0039] Specifically, the dielectric constant ε of the ceramic material is r It is 8 to 13, the quality factor Qf is 50000 to 100000 GHz, and the temperature coefficient of resonant frequency TCF is -30 to -50 ppm / ℃.

[0040] Specifically, the ceramic material can be compatible and co-fired with commonly used metal electrodes Ag or metal electrodes Al.

[0041] For example, the low-loss and low-dielectric molybdenum-based microwave dielectric ceramic material NaSm(MoO4)2 can be sintered at 880°C, and its dielectric constant ε r It is 11.9 (9.8GHz), the quality factor Qf is 91000GHz, the resonant frequency temperature coefficient TCF is -45ppm / ℃, and it can be co-fired with Ag or A1 electrodes.

[0042] The molybdenum-based microwave dielectric ceramic material NaX(MoO4)2 of this embodiment, where X is one or more of Pr, Sm, and Eu, does not require a sintering aid and can be sintered within a relatively low sintering temperature range. It has a relatively low dielectric constant, a relatively high quality factor, and a near-zero resonant frequency temperature coefficient, exhibiting excellent microwave dielectric properties. It can also be co-fired with an Ag electrode or an Al electrode, and has excellent stability when placed in the air, and has the characteristics of a simple chemical composition, being environmentally friendly, non-toxic, and pollution-free.

[0043] This embodiment also provides a method for preparing a molybdenum-based microwave dielectric ceramic material. Figure 1 , Figure 1 A schematic flow chart of a method for preparing a molybdenum-based microwave dielectric ceramic material provided in an embodiment of the present invention. The preparation method comprises the following steps:

[0044] S1. According to the general structural expression formula of ceramic materials, NaX(MoO4)2, Na2CO3, MoO3 and rare earth oxides are weighed as raw materials, wherein X is one or more of Pr, Sm and Eu, and the rare earth oxides include one or more of Pr2O3, Sm2O3 and Eu2O3.

[0045] Specifically, according to the general formula of the ceramic material structure NaX(MoO4)2, weigh the chemical raw materials Na2CO3, MoO3 and rare earth oxide, and prepare Na2CO3, MoO3 and rare earth oxide as raw materials. If the ceramic material is NaPr(MoO4)2, the rare earth oxide is Pr2O3; if the ceramic material is NaSm(MoO4)2, the rare earth oxide is Sm2O3; if the ceramic material is NaEu(MoO4)2, the rare earth oxide is Eu2O3; if the ceramic material is NaPr 0.5 Sm 0.5 (MoO4)2, rare earth oxides are Pr2O3 and Sm2O3; if the ceramic material is NaPr 0.5 Eu 0.5 (MoO4)2, rare earth oxides are Pr2O3 and Eu2O3; if the ceramic material is NaSm 0.5 Eu 0.5 (MoO4)2, rare earth oxides are Sm2O3 and Eu2O3; if the ceramic material is NaPr 1 / 3 Sm 1 / 3Eu 1 / 3 (MoO4)2, rare earth oxides are Pr2O3, Sm2O3 and Eu2O3.

[0046] Among them, Na2CO3, MoO3, Pr2O3, Sm2O3, and Eu2O3 all have analytical purity. For example, the purity of Na2CO3 is 99%, the purity of MoO3 is 99.95%, and the purity of Pr2O3, Sm2O3, and Eu2O3 are all 99.5%.

[0047] Furthermore, before use, the rare earth oxide is placed in a muffle furnace for pretreatment, and the pretreatment condition is to keep it at 700-850° C. for 3-6 hours. Exemplarily, the rare earth oxide is placed in a muffle furnace and kept at 780° C. for 4 hours.

[0048] S2. The raw materials are mixed evenly through a primary ball milling process to obtain a primary ball milled powder.

[0049] Specifically, the raw materials, zirconium balls and anhydrous ethanol (ball milling medium) are added into a ball milling jar at a mass ratio of 1:2:1, and after being sealed, the jar is placed on a planetary ball mill for a first ball milling to mix evenly. The first ball milling parameters include: a rotation speed of 200 to 400 r / min, a time of 3 to 6 hours, and a first ball milling powder is obtained.

[0050] S3, pre-sintering the primary ball-milled powder to obtain a pre-sintered ceramic powder.

[0051] Specifically, the primary ball-milled powder is first dried. For example, the primary ball-milled powder is placed in a common oven and dried at 100° C. for 24 hours; the dried powder is then pre-sintered at 600 to 650° C. for 4 to 8 hours to form a material phase, thereby obtaining a pre-fired ceramic powder.

[0052] S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder.

[0053] Specifically, the ceramic powder can be ground manually, and then put into a ball mill for secondary ball milling to further refine the particle size of the powder. The secondary ball milling parameters include: a rotation speed of 200 to 400 r / min, a time of 3 to 6 hours, and a secondary ball milled powder is obtained.

[0054] S5. The secondary ball-milled powder is pressed and sintered by a pressing and sintering process to obtain a ceramic material.

[0055] Specifically, the secondary ball-milled powder is dried at 100° C. for 24 hours, and 5-8% by weight of polyvinyl alcohol (PVA) is added to the dried powder for granulation. After granulation, the powder is sieved to 60-120 mesh, and pressed into a ceramic embryo at a pressure of 200-300 MPa in an electric press. The ceramic embryo is kept at 500-600° C. for 4-6 hours to remove PVA, and finally kept at 800-900° C. for 6-8 hours for sintering to obtain a low-loss, low-dielectric molybdenum-based, low-temperature sintered microwave dielectric ceramic material.

[0056] Exemplarily, the ceramic green body is a cylindrical ceramic green body with a diameter of 10 mm and a thickness of 5 mm.

[0057] Taking NaPr(MoO4)2 as an example, the chemical reaction process of sintering Na2CO3, MoO3 and Pr2O3 into NaPr(MoO4)2 in this embodiment is as follows:

[0058] Na2CO3=Na2O+CO2

[0059] Na2O+MoO3=Na2MoO4

[0060] Pr2O3+3MoO3=Pr2Mo3O 12

[0061] Na2MoO4+Pr2Mo3O 12 =NaPr(MoO4)2

[0062] This embodiment adopts the classic solid phase reaction method to prepare the molybdenum-based microwave dielectric ceramic material, which has a simple chemical composition, a simple preparation process, is environmentally friendly, non-toxic and pollution-free, and shows good practical application and sustainable development prospects.

[0063] Furthermore, this embodiment provides an application of a molybdenum-based microwave dielectric ceramic material in a low temperature co-fired ceramic (LTCC) substrate.

[0064] Specifically, the molybdenum-based microwave dielectric ceramic material of this embodiment can be co-fired with Ag or Al electrodes, can be used to prepare low-temperature co-fired ceramic (LTCC) substrates, and further used in the fields of microwave resonators, filters, and flat antennas.

[0065] This embodiment further illustrates the molybdenum-based microwave dielectric ceramic material and the preparation method thereof through the following examples.

[0066] Example 1

[0067] The raw materials Na2CO3, Pr2O3 and MoO3 of analytical purity were weighed in a molar ratio of 1:1:4, and the weighed Pr2O3 was placed in a muffle furnace and kept warm at 780℃ for 4h. Then the prepared raw materials, zirconium balls and anhydrous ethanol were ball milled once in a mass ratio of 1:2:1, with a ball milling speed of 200-400r / min for 4h to obtain a primary ball milled powder. The primary ball milled powder was placed in an ordinary oven and dried at 100℃ for 24h, and then pre-calcined at 600℃ for 4h to obtain a pre-calcined ceramic powder, which was a block sample. The pre-calcined ceramic powder was crushed and then ball milled twice, with a secondary ball milling speed of 200-400r / min for 4h to obtain a secondary ball milled powder. The secondary ball-milled powder is dried at 100°C for 24 hours, and then 6% by weight of PVA is added to the dried powder for granulation. After double screening through 60-mesh and 120-mesh sieves, it is pressed into a cylindrical ceramic embryo under a pressure of 200 MPa, and kept at 550°C for 6 hours to remove the PVA. Finally, 740°C, 770°C, 800°C, 830°C, 860°C, 890°C, and 920°C are selected within the range of 740-920°C, and sintered in air for 6 hours to obtain low-temperature sintered microwave dielectric ceramic material NaPr(MoO4)2.

[0068] Furthermore, the Na sintered at 740-920°C was measured. 0.5 Pr 0.5 The density and relative density spectra of MoO4 ceramics were analyzed by closed cavity resonance TE method using a network analyzer (4990A Agilent) and a temperature oven (DELTA 9023, Delta Design). 01δ The model tested Na sintered at 740-920℃ 0.5 Pr 0.5 Microwave dielectric properties of MoO4 ceramic samples, where the calculation formula of the resonant frequency temperature coefficient TCF is as follows:

[0069]

[0070] In the formula, f 25 is the resonant frequency of the sample at 25°C, in GHz, f 85 is the resonant frequency of the sample at 85°C, in GHz.

[0071] See also Figure 2 , Figure 2 The Na sintered at 740-920°C provided in the embodiment of the present invention 0.5 Pr 0.5Schematic diagram of the density and relative density of MoO4 ceramics changing with temperature. It can be seen that with the increase of sintering temperature, the density and relative density of the ceramics gradually increase. The density of the sample reaches the maximum value at 830℃, and then begins to decrease slightly. This should be caused by the closed pores in the abnormally grown grains after continuous heating.

[0072] See also Figure 3 , Figure 3 The Na sintered at 740-920°C provided in the embodiment of the present invention 0.5 Pr 0.5 Schematic diagram of the microwave dielectric properties of MoO4 ceramics changing with sintering temperature. As the sintering temperature increases, the relative dielectric constant ε r The Qf value varies between 11.8 and 12.6, and increases first and then decreases with the sintering temperature, with the maximum value being about 73000 GHz (sintering temperature ST = 830°C). However, the dependence of TCF value on sintering temperature is not as sensitive as other microwave dielectric parameters.

[0073] After testing, the ceramic material NaPr(MoO4)2 was sintered into porcelain in air at 830℃, and the microwave dielectric properties at 830℃ reached the following indicators: the dielectric constant ε in the microwave frequency band (9.6GHz) r It is 12.3, the quality factor Q is 7260, the corresponding Qf is 73000GHz, and the resonant frequency temperature coefficient TCF under microwave is -42ppm / ℃ (25~85℃).

[0074] Example 2

[0075] The raw materials Na2CO3, Sm2O3 and MoO3 of analytical purity were weighed in a molar ratio of 1:1:4, and the weighed Sm2O3 was placed in a muffle furnace and kept warm at 780℃ for 4h. Then the prepared raw materials, zirconium balls and anhydrous ethanol were ball milled once in a mass ratio of 1:2:1, with a ball milling speed of 200-400r / min for 4h to obtain a first ball milled powder. The first ball milled powder was placed in an ordinary oven and dried at 100℃ for 24h, and then pre-calcined at 650℃ for 4h to obtain a pre-calcined ceramic powder, which was a block sample. The pre-calcined ceramic powder was crushed and then ball milled twice, with a second ball milling speed of 200-400r / min for 4h to obtain a second ball milled powder. The secondary ball-milled powder is dried at 100°C for 24 hours, and then 8% by weight of PVA is added to the dried powder for granulation. After double screening through 60-mesh and 120-mesh sieves, it is pressed into a cylindrical ceramic embryo under a pressure of 200 MPa, and kept at 550°C for 6 hours to remove the PVA. Finally, 740°C, 770°C, 800°C, 830°C, 860°C, 890°C, 920°C, and 950°C are selected within the range of 740-950°C, and the powder is sintered in air for 6 hours to obtain low-temperature sintered microwave dielectric ceramic material NaSm(MoO4)2.

[0076] Furthermore, the density and relative density spectrum of NaSm(MoO4)2 ceramics sintered at 740-950°C were measured, and the closed-cavity resonance TE method was used using a network analyzer (4990A Agilent) and a temperature oven (DELTA 9023, Delta Design). 01δ The microwave dielectric properties of the samples were tested at 740-950℃.

[0077] See also Figure 4 , Figure 4 A schematic diagram of the density and relative density of NaSm(MoO4)2 ceramics sintered at 740-950°C as a function of temperature provided in the embodiment of the present invention. It can be seen that with the increase of sintering temperature, the density and relative density of the ceramic gradually increase, the density of the sample reaches a maximum value at 830°C, and then begins to decrease slightly, which should be caused by the closed pores in the abnormally grown grains after continuous heating.

[0078] See also Figure 5 , Figure 5 Schematic diagram of microwave dielectric properties of NaSm(MoO4)2 ceramic sintered at 740-950°C as a function of temperature. rThe Qf value increases first and then decreases slowly with the sintering temperature, and the maximum value is about 91000 GHz (sintering temperature ST = 890 ° C). The dependence of TCF value on sintering temperature is not as sensitive as other microwave dielectric parameters.

[0079] After testing, the microwave dielectric properties of the ceramic material NaSm (MoO4) 2 have reached the following indicators: NaSm (MoO4) 2 is sintered into porcelain in air at 890 ° C, and the dielectric constant ε in the microwave frequency band (9.8 GHz) is r It is 11.9, the quality factor Q is 7800, the corresponding Qf is 91000GHz, the resonant frequency temperature coefficient TCF under microwave is -45ppm / ℃ (25~85℃), and it shows good air stability.

[0080] Example 3

[0081] The raw materials Na2CO3, Eu2O3 and MoO3 of analytical purity are weighed in a molar ratio of 1:1:4, and the weighed Eu2O3 is placed in a muffle furnace and kept warm at 780℃ for 4h. Then the prepared raw materials, zirconium balls and anhydrous ethanol are ball milled once in a mass ratio of 1:2:1, the ball milling speed is 200-400r / min, and the time is 4h to obtain the first ball milling powder. The first ball milling powder is placed in an ordinary oven and dried at 100℃ for 24h, and then pre-calcined at 600℃ for 4 hours to obtain the pre-calcined ceramic powder, which is a block sample. The pre-calcined ceramic powder is crushed and then ball milled twice, the second ball milling speed is 200-400r / min, and the time is 4h to obtain the second ball milling powder. The secondary ball-milled powder is dried at 100°C for 24 hours, and then 5% by weight of PVA is added to the dried powder for granulation. After double screening through 60-mesh and 120-mesh sieves, it is pressed into a cylindrical ceramic embryo under a pressure of 300 MPa, kept at 550°C for 6 hours to remove the PVA, and finally sintered at 860°C in air for 6 hours to obtain low-temperature sintered microwave dielectric ceramic material NaEu(MoO4)2.

[0082] The closed-cavity resonance method was used to measure the TE signal using a network analyzer (4990A Agilent) and a temperature chamber (DELTA 9023, Delta Design). 01δ The microwave dielectric properties of the samples were tested in this mode.

[0083] After testing, the microwave dielectric properties of the ceramic material NaEu(MoO4)2 have reached the following indicators: NaEu(MoO4)2 is sintered into porcelain in air at 860℃, and the dielectric constant ε in the microwave frequency band (9.5GHz) is rIt is 11.3, the quality factor Q is 6300, the corresponding Qf is 61000GHz, and the resonant frequency temperature coefficient TCF under microwave is -38ppm / ℃ (25~85℃).

[0084] See also Figure 6 , Figure 6 XRD patterns of samples in Example 1, Example 2 and Example 3 provided in the present invention, wherein Example 1 is a sample sintered at 820°C, and Example 2 is a sample sintered at 890°C. After comparison with the standard card, it was found that Na 0.5 Pr 0.5 MoO4、Na 0.5 Sm 0.5 MoO4 and Na 0.5 Eu 0.5 No other second phase was observed in the XRD spectrum of MoO4 ceramics, and all characteristic diffraction peaks can be attributed to the tetragonal crystal system, with a CaWO4 / ABO4 scheelite structure and a corresponding space group of I41 / a.

[0085] Through Examples 1, 2, and 3, it can be seen that the NaX(MoO4)2 (X = one or more of Pr, Sm, and Eu) system proposed in this example has excellent microwave dielectric properties (ε r =8~13, Qf=50000~100000GHz, TCF=-30~-50ppm / ℃). The low-loss and low-dielectric molybdenum-based microwave dielectric ceramic material of this embodiment can not only be sintered at a relatively low temperature, but also has excellent microwave dielectric properties; it has good stability when placed in the air, has the characteristics of simple chemical composition, simple preparation process, environmental protection, non-toxicity and pollution-free; it can be co-fired with Ag electrode or Al electrode, and is suitable for the preparation of low-temperature co-fired ceramic substrates, and has wide application potential in the fields of microwave resonators, filters and planar antennas.

[0086] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A molybdenum-based microwave dielectric ceramic material, characterized in that: The general structural formula of the ceramic material is NaX(MoO4)2, wherein X is one or more of Pr, Sm, and Eu.

2. The molybdenum-based microwave dielectric ceramic material according to claim 1, characterized in that: The sintering temperature of the ceramic material is 800-900°C.

3. The molybdenum-based microwave dielectric ceramic material according to claim 1, characterized in that: The dielectric constant of the ceramic material is 8 to 13, the quality factor is 50,000 to 100,000 GHz, and the resonant frequency temperature coefficient is -30 to -50 ppm / °C.

4. A method for preparing a molybdenum-based microwave dielectric ceramic material, characterized in that: Includes steps: S1. According to the general formula NaX(MoO4)2 of the ceramic material structure, weigh Na2CO3, MoO3 and rare earth oxide as raw materials, wherein X is one or more of Pr, Sm and Eu, and the rare earth oxide includes one or more of Pr2O3, Sm2O3 and Eu2O3; S2, mixing the raw materials uniformly through a primary ball milling process to obtain a primary ball milled powder; S3, pre-sintering the primary ball-milled powder to obtain a pre-sintered ceramic powder; S4, performing secondary ball milling on the ceramic powder to obtain secondary ball milled powder; S5. The secondary ball-milled powder is pressed and sintered by a pressing and sintering process to obtain the ceramic material.

5. The method for preparing a molybdenum-based microwave dielectric ceramic material according to claim 4, characterized in that: Step S1 includes: The rare earth oxide is placed in a muffle furnace and kept at 700-850° C. for 3-6 hours.

6. The method for preparing a molybdenum-based microwave dielectric ceramic material according to claim 4, characterized in that: Step S2 includes: The raw materials, zirconium balls and anhydrous ethanol are added into a ball mill in a mass ratio of 1:2:1 and ball milled once to mix them evenly. The parameters of the first ball milling include: a rotation speed of 200 to 400 r / min and a time of 3 to 6 hours to obtain the first ball milled powder.

7. The method for preparing a molybdenum-based microwave dielectric ceramic material according to claim 4, characterized in that: Step S3 includes: The once ball-milled powder is dried, and the dried powder is pre-sintered at 600-650° C. for 4-8 hours to obtain a pre-sintered ceramic powder.

8. The method for preparing a molybdenum-based microwave dielectric ceramic material according to claim 4, characterized in that: Step S4 includes: The ceramic powder is first ground into powder, and then put into a ball mill for secondary ball milling. The secondary ball milling parameters include: a rotation speed of 200 to 400 r / min and a time of 3 to 6 hours to obtain the secondary ball milled powder.

9. The method for preparing a molybdenum-based microwave dielectric ceramic material according to claim 4, characterized in that: Step S5 includes: The secondary ball-milled powder is dried, and 5-8% by weight of PVA is added to the dried powder for granulation. After granulation, the powder is sieved to 60-120 mesh, and pressed into a ceramic green body at a pressure of 200-300 MPa in an electric press, and the ceramic green body is kept at 500-600° C. for 4-6 hours to remove PVA, and finally kept at 800-900° C. for 6-8 hours for sintering to obtain the ceramic material.

10. Application of a molybdenum-based microwave dielectric ceramic material in a low-temperature co-fired ceramic substrate.

Citation Information

Patent Citations

  • Aluminum molybdate-based microwave dielectric composite ceramic and preparation method thereof

    CN108727023A